2012
DOI: 10.2165/11630850-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Pain Medication and Global Cognitive Functioning in Dementia Patients with Painful Conditions

Abstract: Undertreatment of pain in dementia seems to be independent of global cognitive functioning. The use of observational scales, to increase the awareness of other signs of pain, e.g. physical inactivity and behavioural disturbances, is recommended. Even if there is no obvious cause for behavioural disturbances, treatment with relatively mild pain medication should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 26 publications
1
15
0
7
Order By: Relevance
“…Pain in patients with dementia has been poorly evaluated in relation to the ACB. Moreover, the hospital setting has seldom been considered, as most studies were based in community and nursing home settings …”
Section: Discussionmentioning
confidence: 99%
“…Pain in patients with dementia has been poorly evaluated in relation to the ACB. Moreover, the hospital setting has seldom been considered, as most studies were based in community and nursing home settings …”
Section: Discussionmentioning
confidence: 99%
“…Patients with altered cognition comprise a significant proportion of nursing home residents, and proper assessment of pain with appropriate treatment options in patients with dementia has the potential to reduce negative behaviors. 20 Our study also demonstrated the key role that family members play in decision making and overall success of pain interventions. 21 Family members of residents view themselves as advocates for nursing home residents.…”
Section: Discussionmentioning
confidence: 52%
“…However, people with intellectual disability and dementia may lose the ability to recognise and report their pain experience due to their disability or as the dementia progresses, which makes pain recognition and treatment more challenging. Thereby, they are less likely to have their pain needs met adequately (Cleary & Doody, 2017a;Doody & Bailey, 2017;Kerr et al, 2006;Kerr, Cunningham, & Wilkinson, 2011;Plooij, Spek, & Scherder, 2012). The inadequate recognition of a person's pain experience can result in diagnostic overshadowing; whereby, behavioural changes displayed are attributed to the intellectual disability or dementia rather than considering other causes such as pain (Kerr et al, 2006(Kerr et al, , 2011.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…generally the evidence identifies that carers (formal and informal) do not adequately recognise or consider pain as a possible cause for changes in presentation (Cleary & Doody, 2017a;Plooij et al, 2012).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation